Cardiovascular disease risk is only elevated in hypertensive, formerly preeclamptic women. (20th August 2014) - Breetveld, NM; Ghossein‐Doha, C; van Kuijk, SMJ; van Dijk, AP; van der Vlugt, MJ; Heidema, WM; Scholten, RR; Spaanderman, MEA
<x xml:space="preserve">Abstract</x> Objective To analyse the predicted 10‐ and 30‐year risk scores for cardiovascular disease (CVD) in patients who experienced preeclampsia (PE) 5–10 years previously compared with healthy parous controls. Design Observational study. Setting Tertiary referral hospital in the Netherlands. Population One hundred and fifteen patients with a history of PE and 50 controls. PE patients were categorised into two groups, hypertensive (n = 21) and normotensive (n = 94), based on use of antihypertensive medication, and next categorised into subgroups based on the onset of PE: early‐onset PE (n = 39) and late‐onset PE (n = 76). Methods All participants underwent cardiovascular risk screening 5–10 years after index pregnancy. We measured body mass, height and blood pressure. Blood was analysed for fasting glucose, insulin and lipid levels. All participants completed a validated questionnaire. The 10‐ and 30‐year Framingham risk scores were calculated and compared. Main outcome measures Estimated Framingham 10‐ and 30‐year risk scores for CVD. Results The overall 10‐ and 30‐year CVD median risks weighing subjects' lipids were comparable between formerly PE women and controls; 1.6 versus 1.5% (P = 0.22) and 9.0 versus 9.0% (P = 0.49), respectively. However, hypertensive formerly PE women have twice the CVD risk as normotensive formerly PE women: 10‐ and 30‐year CVD median risks were 3.1 versus 1.5% (P < 0.01) and 19.0% versus 8.0% (P < 0.01), respectively. Risk estimates based on BMI rather than lipid profile show comparable results. Early‐onset PE clustered more often in the hypertensive formerly PE group and showed significantly higher 10‐ and 30‐year CVD risk estimates based on lipids compared with the late‐onset PE group: 1.7 versus 1.3% (P < 0.05) and 10.0 versus 7.0% (P < 0.05), respectively. Conclusions Women who are hypertensive after preeclampsia, have a twofold risk of developing CVD in the next 10–30 years. Formerly PE women who are normotensive in the first 10 years after their preeclamptic pregnancy have a comparable future cardiovascular risk to healthy controls.